Qualitative perspectives from Kinova® Jaco® robotic arm owners: understanding daily device usage. - Styler, Breelyn Kane; Wang, Eileen; Ding, Dan (Disability & Rehabilitation, 2025)
Purpose: Although the benefits of Assistive Robotic Manipulators (ARMs) have been recognized since their emergence over the past two decades, the number of ARM owners remains limited, though expected to grow. This study interviews current owners to gather their perspectives and uses the Human Activity Assistive Technology (HAAT) model to understand their usage experiences with ARMs. Materials and methods: A semi-structured remote interview study was conducted with robotic arm owners ( ≥ 3 months). Pre-interview surveys collected demographics and common tasks with the robotic arm. Thematic analysis identified key themes. Results: Eleven ARM owners were recruited and gave examples of the Kinova® Jaco® robotic arm being a life-changing benefit promoting independence which emerged as a theme. Additional themes emerged around operation, caregiver influence, environment, and training. Common tasks included drinking and opening doors. Design recommendations focused on modular attachments, adjustable speed, smoother operation, intuitive control, and enhanced safety. Conclusion: We performed a qualitative interview and drew conclusions guided by the HAAT model to better understand interactions between the user, the robotic arm, and contexts of its use for manipulation tasks. The insights gained can better inform prospective owners and guide future research in assistive robotics. IMPLICATIONS FOR REHABILITATION: Gaining insight into the benefits and concerns of current Jaco robotic arm owners can inform future research, design, and the acceptance of wheelchair-mounted assistive robotic arms. Robotic arm owners require support and follow-up from practitioners, caregivers, and peers to enhance their robotic arm operation skills and increase usage. Broader contextual, human, and activity-related factors influence the effective use and adoption of assistive robotic arms.